2004
DOI: 10.1007/s00705-003-0259-6
|View full text |Cite
|
Sign up to set email alerts
|

Complete nucleotide sequences of genome segments 1 and 3 of Rosellinia anti-rot virus in the family Reoviridae

Abstract: The nucleotide sequences of genome segments 1 and 3 of Rosellinia anti-rot virus (RArV) from a hypovirulent isolate, W370, of the plant pathogen Rosellinia necatrix were determined. The complete nucleotide sequence of the genome segment 1 encoded a putative RNA-dependent RNA polymerase (RDRP). The deduced amino acid sequence of RDRP of RArV showed 29% identity with RDRPs of Colorado tick fever virus (CTFV) and European Eyach virus (EYAV) in the genus Coltivirus, and identities of 23-21% with members of the gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(14 citation statements)
references
References 15 publications
1
12
0
1
Order By: Relevance
“…Genus Mycoreovirus was then created to accommodate three species, Mycoreovirus 1 to Mycoreovirus 3 (including well-characterized representative isolates MyRV1 to MyRV3, respectively). MyRV1 and -2 were isolated from Cryphonectria parasitica, and MyRV3 from Rosellinia necatrix (Hillman and Suzuki, 2004;Wei et al, 2004). All mycoreoviruses confer hypovirulence to their respective natural hosts.…”
Section: Reoviridae (Dsrna)mentioning
confidence: 99%
“…Genus Mycoreovirus was then created to accommodate three species, Mycoreovirus 1 to Mycoreovirus 3 (including well-characterized representative isolates MyRV1 to MyRV3, respectively). MyRV1 and -2 were isolated from Cryphonectria parasitica, and MyRV3 from Rosellinia necatrix (Hillman and Suzuki, 2004;Wei et al, 2004). All mycoreoviruses confer hypovirulence to their respective natural hosts.…”
Section: Reoviridae (Dsrna)mentioning
confidence: 99%
“…6Q). It has been predicted that sense-strandspecific inverted repeat and panhandle structures exist between the 5= and 3= termini of genome segments of RnQV1, RnVV1, and RnMyRV3 (29,34,40,61); therefore, these secondary structures might be diced. In contrast, we found that vsRNA peaks were densely distributed at the 5= region of both RnPV1-S1 and RnPV1-S2 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Esses segmentos são encapsidados em diferentes partículas icosaédricas de capsídeo duplo, com 80 nm de diâmetro (HILLMAN; SUZUKI, 2005;WEI et al, 2004). Todas as espécies relatadas conferem hipovirulência a seus hospedeiros (GHABRIAL et al, 2015).…”
Section: Taxonomia De Micovírusunclassified